Motion Control and Path Planning of Marine Vehicles - Xing, Bowen; Li, Bing (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the continuous improvement of artificial intelligence and sensing technologies, the marine field is ushering in unprecedented change. In this wave of change, the design and application of marine transportation have become significant tools for promoting the marine economy and environmental protection. Motion control and path planning have become key technologies to ensure that marine transportation vehicles operate efficiently and intelligently in complex marine environments. Therefore, this Special Issue focuses on motion control and path planning for marine vehicles and explores how autonomous underwater vehicles (AUVs), surface unmanned vehicles (USVs), and deep-sea landers (DSLVs) can play a key role in the oceans through optimization strategies and new approaches. We will delve into the application of intelligent and autonomous motion control systems on marine vehicles, and the innovation and optimization of path-planning techniques. In this Special Issue, we brought together the latest results from experts and researchers, aiming to share their cutting-edge research in motion control and path planning for marine vehicles. We expect that the presentation of these papers will provide new ideas and solutions to promote marine science and technology development and application. Finally, we would like to convey our most profound gratitude to the staff of MDPI Books and the editorial team of Marine Science and Engineering, in particular the assistant editors, talented authors, and diligent reviewers.